Preparing the functional biomaterial with osteogenic bioactivities by incorporating annealing pretreated silk fiber and iron oxide nanoparticles - Wang, Peng; Wang, Hengda; Wang, Xucai; Gu, Jiayu; Huang, Caoxing; Sun, Jianfei (Frontiers in Bioengineering and Biotechnology, 2025)
Silk fiber (SF), a kind of bio-fiber from biomass protein fibers with biocompatibility and mechanical properties, has been widely utilized in biomedical engineering. However, SF-based bio-scaffolds often encounter challenges in promoting osteogenesis within bone tissue engineering (BTE) applications. In this study, SF-based composites were constructed via the solution casting method in the presence of IONPs (SFFC-IONPs), followed by annealing-induced self-assembly to form magnetic SF annealing films (SFFCA-IONPs). Three types of IONPs loaded SF films (SFFCA-50, SFFCA-100, and SFFCA-200) were prepared by altering the feeding IONPs (50 μg/mL, 100 μg/mL, and 200 μg/mL). Results demonstrated that SFFC films primarily exhibited random coil structures and were water-soluble, while SFFCA films demonstrated the formation of silk II structures and became water-insoluble. The incorporation of IONPs significantly enhanced the porosity, mechanical strength, and thermal stability of the SFFCA films. Furthermore, the SFFCA-IONPs films not only exhibited excellent biocompatibility but also demonstrated enhanced osteo-inductive properties, as evidenced by increased alkaline phosphatase (ALP) activity, enhanced mineralized nodule formation, and upregulation of osteogenic gene expression. This study presents a promising bio-based material with significant potential for use as a scaffold in BTE applications.